S243. RACIAL AND ETHNIC DIFFERENCES IN PATHWAY TO CARE AND BASELINE CHARACTERISTICS IN EARLY INTERVENTION SERVICES FOR PSYCHOSIS IN NEW YORK STATE. (18th May 2020) - van der Ven, Els; Smith, Stephen; Rawlins, Yasmin; Nossel, Ilana; Basaraba, Cale; Wall, Melanie; Scodes, Jennifer; Veling, Wim; Marino, Leslie; Dixon, Lisa
Abstract: Background: The racial and ethnic background of individuals with psychosis may shape their pathway to early intervention services and clinical presentation at admission. Studies from Europe and Canada demonstrate that black minority patients with first-episode psychosis experience a more adverse and coercive pathway to care. The extent to which these findings can be extrapolated to the US context is unknown. The aims of this study are (1) to compare baseline contextual and clinical characteristics, and (2) to examine care pathways by race and ethnicity among young people with psychosis in early intervention services. Methods: This study included individuals with a recent-onset (<2 years) psychosis aged 16 to 30 years enrolled at 19 early intervention programs across New York State. Clinicians collected data on pathway to care, demographic, social and clinical variables at program entry. Level of functioning was assessed using the social, occupational and symptomatic functioning subscales of the MIRECC GAF. Results: The sample included 767 individuals with a non-Hispanic white (n=209, 27.2%), non-Hispanic black (277, 36.1%), Hispanic (218, 28.4%), or Asian (63, 8.2%) racial/ethnic background. Compared to non-Hispanic white, minority individuals were more likely to have public or no insurance and, overall, had a lower level of completed education. In terms of pathway to care, a lower proportion of non-Hispanic black (65.7%) and Asian (58.7%) participants had previously used mental health services compared to the non-Hispanic white group (78.0%). In contrast, psychiatric hospital or emergency department admissions in the 90 days prior to program enrollment were more frequent among all minority groups in comparison to the non-Hispanic white group. There were no significant differences by race and ethnicity in the level of symptoms or social functioning at baseline. Discussion: Our findings suggest a pattern of mental health service use among minority groups with psychosis characterized by less mental health contacts but more inpatient and emergency care prior to the initiation of early intervention services. This trend could be partly explained by racial and ethnic patterning at the contextual level, including financial barriers to care, less so by racial/ethnic differences in illness severity. Our findings are consistent with evidence demonstrating an overrepresentation of minority individuals, especially African-Americans, in psychiatric emergency services suggesting a gap in unmet mental health need among minority populations in the US.